Etiology of short stature in children and adolescents: experience at a tertiary care hospital in Bangladesh - Jasim, Sabrina; Mohsin, Fauzia; Islam, Nasreen; Halder, Amrita Lal; Hossain Mollah, Md Abid (BIRDEM Medical Journal, 2022)
Background: Short stature can cause psychosocial problems both in parents and children. It can be a normal variant or secondary to an underlying pathological condition. It is necessary to evaluate cause of short stature and thus to decide whether further management needed. This study aimed to determine the causes of short stature in children and adolescents. Methods: This cross-sectional study was done at the paediatric endocrine out patient department, BIRDEM General Hospital 2, Dhaka from January to December 2019. A total 175 patient with short stature who fulfilled the inclusion criteria were recruited. Detailed history, physical examinations including anthropometric measurements and relevant investigations were recorded. Results: The mean age of the children was 9 ± 4 years, with female preponderance (female: male 1.27:1). Majority of the children had normal variation of growth (29%). Systemic illness and non-endocrine causes were found in 27.4%, endocrine cause in 26.85%, 13.7 % cases had dysmorphic features and idiopathic short stature was found in 2.85% cases. Familial short stature (FSS) was the most common cause (20.57%) followed by hypothyroidism (13.14%), familial short stature co-existing with nutritional problem (8.6%), growth hormone deficiency (7.4%), Turner syndrome (6.28%). Other causes that contributed for short stature in our study included constitutional delay of growth and puberty (CDGP) (2.85%), FSS coexisting with CDGP (5.7%) and systemic diseases and chromosomal abnormalities. Conclusions: The majority of short stature in children had normal variations of growth. Potentially treatable causes such as hypothyroidism, growth hormone deficiency, nutritional problem, Turner syndrome etc. accounted for a considerable percentage of short stature in our study. BIRDEM Med J 2022; 12(2): 117-123